2011
DOI: 10.1186/1477-7827-9-124
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin levels in relation to circulating cytokines, chemokines, adhesion molecules and angiogenic factors in normal pregnancy and preeclampsia

Abstract: ObjectiveIn this study, we determined circulating levels of C-reactive protein, several cytokines, chemokines, adhesion molecules and angiogenic factors along with those of leptin in healthy non-pregnant and pregnant women and preeclamptic patients, and investigated whether serum leptin levels were related to the clinical characteristics and measured laboratory parameters of the study participants.MethodsSixty preeclamptic patients, 60 healthy pregnant women and 59 healthy non-pregnant women were involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 65 publications
(63 reference statements)
6
80
2
1
Order By: Relevance
“…There is controversy with respect to the concentrations of these proteins in PE [21][22][23][24][25][26][27][28]. On the other hand, we observed that the maternal concentrations of VCAM-1 were higher in PE.…”
Section: Discussionmentioning
confidence: 61%
“…There is controversy with respect to the concentrations of these proteins in PE [21][22][23][24][25][26][27][28]. On the other hand, we observed that the maternal concentrations of VCAM-1 were higher in PE.…”
Section: Discussionmentioning
confidence: 61%
“…Increased BMI is also a risk factor for isolated gestational proteinuria during normal term pregnancy [35]. A recent study has suggested a possible pathogenic mechanism of increased leptin levels and activation of pro inflammatory cytokines in PE [36]. In this study serum leptin levels in relation to circulating cytokines, chemokines, adhesion molecules and angiogenic factors in normal pregnancy and preeclampsia.…”
Section: International Journal Ofmentioning
confidence: 75%
“…Furthermore, Masuyama et al reported significant elevation of leptin in early and late onset preeclampsia compared to controls [22], while Molvarec et al found no statistically significant difference in serum leptin concentration between late and early onset preeclampsia and among peeclamptic patients with mild and severe form of the disease [35]. In the current study, it is also revealed that leptin decreased significantly in the early post partum period in group (A) (15.3 ± 3.19, p = 0.001*) and group (B) (11.2 ± 2.68, p = 0.002*) which is in line with the results published by Mc Carthy et al [30], and Saylik et al [36], but we did not detect any significant difference between both groups in postpartum maternal serum leptin levels.…”
Section: Discussionmentioning
confidence: 98%